Kedudukan dan Pemahaman Sunnah al-Ḥadīth sebagai Sumber Hukum Islam: Pendekatan Konseptual dan Metodologis - Murtadlo, Mohammad Chusein; Nasrulloh, M. Zidan (TSAQOFAH, 2026)
The sunnah al-hadith is the second source of law after the Al-Qur’an and plays a central role in the process of legal derivation (istinbat hukum); however, its application as legal evidence cannot be carried out instantaneously, because understanding hadith requires verification of sanad, examination of matan, and clarity regarding the historical context. This article aims to explain the status of sunnah al-hadith as a source of Islamic law by reviewing its basic concepts, definitions, and the epistemological grounds that justify its acceptance as dalil syar‘i, while also outlining the fundamental methods for understanding and applying hadith in the process of legal determination. This study employs a library research method by examining classical literature, particularly al-Risalah by Imam al-Shafi‘i and primary hadith compilations, in conjunction with relevant contemporary academic references. The findings show that the legitimacy of sunnah al-hadith as a source of law rests on strong textual and rational foundations, its diverse functions in relation to the Al-Qur’an (explaining, reinforcing, restricting, and particularizing), and a set of ushuliyyah principles that regulate the conditions of authenticity, interpretive rules, and priority in the use of legal evidence. These findings affirm the urgency of mastering the basic methodology of hadith understanding from sanad and matan verification to the application of istidlal rules as a foundational requirement for students and scholars of Islamic law to optimize the role of sunnah al-hadith as an authoritative and proportionate source of law in contemporary istinbat practice.